Approaches adopted in the teaching of poetry for the upper secondary school students in Tawau town area - Lim, Bridget Suk Han; Omar, Suhaida (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
The main aim of conducting this study was to investigate the various techniques adopted among the teachers teaching poetry in the upper secondary schools in the Tawau town area. The researcher would like to find out the types of techniques that are preferred the most as well as the least in the teaching of poetry to the upper secondary school students and examine the factors that affect the selection of these techniques.The techniques put forward in this study that the teachers should have been exposed to are Language Based Approach, Personal Response Based Approach, Stylistic Approach, Information Based Approach and Moral Philosophical Approach.This survey research targeted forty-five English language teachers teaching the literature component to secondary four and five students at seven secondary schools in the Tawau town area. Three research instruments which were utilized in this study are the questionnaire, classroom observation and the interview. The result of the questionnaire was later triangulated using classroom observation and the interview,which was conducted with one representative (teacher) who was randomly selected from each school. It was found that the Moral Philosophical Approach was the most preferred while the Stylistic Approach was the least preferred technique.It was also discovered that some techniques advocated under each approach specified in this study were more preferred than others. Hence, the information gained has been used especially by the researcher and her colleagues in the teacher training college to propose practical suggestions and recommendations on how to improve the teaching processes using poetry